Analysis of the Principal's Leadership Strategy with the Trilogy Ki Hajar Dewantara Concept in Improving the Quality of Education at Bajing Kulon 04 Elementary School Kroya District, Cilacap Regency - Surata Surata; Ine Kusuma Aryani (Green Publisher, 2024)
The Principal has an important role in leading, planning, developing, supervising and evaluating school activities, with the concept of the Ki Hajar Dewantara trilogy can improve the quality of education at SD Negeri Bajing Kulon 04, Kroya District, Cilacap Regency. The purpose of the study was to determine the principal's strategy in implementing the concept of the leadership trilogy of Ki Hajar Dewantara, to improve the quality of education at SD Negeri Bajingkulon 04, Kroya District, Cilacap Regency. This research uses a qualitative approach with a descriptive method. Data collection is obtained through interviews, observation, and documentation. The subjects of the study were principals, teachers, and supervisors. The results of the study were found, namely the principal's strategy was prepared by the principal with the approval of educators and education staff who conveyed during the meeting, The obstacles faced by the principal were in the form of teachers who still arrived late and did not implement the rules in an orderly manner, lack of teacher concern when facing the acceptance of new students, The principal's solution applied provided an example, with the concept of the Ki Hajar Dewantara trilogy, with the character and behavior of Ki Hajar Dewantara setting an example for teachers, providing direction/coaching both personally and through work meetings, fulfilling the required school infrastructure, collaborating with school supervisors in coaching programs, involving teachers in participating in KKG.